O sucesso: uma análise do discurso publicitário de/sobre o sucesso em centros universitários privados. - Lima, Victor Hugo D'Albuquerque (2022)
The present thesis contemplates the analysis of the utterance “Sucesso”, its discursive formation and effects of meaning in the publicity of the main private University Centers of Pernambuco - in its circulation and strength in the media, from the perspective of the theory and methodological procedure of the French AD, identifying the power of the market to ideologically challenge the subject, assuming that the text is the material place where the relationship between language and ideology and the production of effects takes place. It aims to analyze the discursive memory in the advertising of Brazilian private higher education institutions, observing possible regularities in the use of Success and its meaning effects, correlating the advertising language as an expression of the dominant ideological, political and economic formation, which make up its production conditions. and interdiscourse derivatives; point to the effects of advertising discourse as a spectacle in our social formation; to discuss the relationships between the ideological interpellations of advertisements (corpus), anticipation and their possible effects on the subject, relating to the media and the market. The Methodology consisted of collecting and analyzing advertising pieces and institutional communications published in the last five years and collected on Instagram® from the seven main private University Centers in Recife-PE, according to the MEC 2021 IGCs ranking: (Unibra; Unit; UniFBV; UniNassau; UniNabuco; UniFG; Estácio), of quality recognized by the MEC with IGCs 3, 4 or 5. The concepts of Discursive Formation, Discursive Memory, Interdiscourse, Production Conditions, Imaginary Formation, Paraphrase were primarily mobilized for the analysis. and Polysemy. Using AD, the discourses of advertising pieces and institutional communications of these private higher education institutions (Corpus) that approach success were analyzed, structuring a comparative, registering similarities and regularities and identifying their alignment with the capitalist FD of success. As a result of this research, one can observe the alignment of the discourses of the various private HEIs analyzed with the 'capitalist FD of success', a concept developed throughout this work, showing a regularity in the discursive promise.